ANALISA DAN PERANCANGAN SISTEM POS MENGGUNAKAN METODE EXTREME PROGRAMMING DENGAN PHP NATIVE BERBASIS WEBSITE - Rahmat Ali Saif (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Toko Amar is one type of business that utilizes the development of this technology especially in the sales transaction section and stock management. Previously the sales transaction process and management of existing stock items at Toko Amar still using a manual system, therefore an information system in the form of a website-based point of sale system was created, where the transaction process and management of stock items will be computerized and well recorded. In the process of designing POS system at Toko Amar using Extreme Programming method, because this Extreme Programming method is considered quite simple and very compatible with the POS system that has been created. The result of this research is a Point of Sale system whose usefulness is in accordance with transaction needs and stock management at Toko Amar, that is a more efficient transaction process and more well-recorded stock items.